2017
DOI: 10.1177/0091217417720896
|View full text |Cite
|
Sign up to set email alerts
|

A guide to psychopharmacological treatment of patients with intellectual disability in psychiatry

Abstract: Background Subjects with intellectual disability are at increased risk of having comorbid psychiatric disorders and worse response to psychotherapeutic and psychopharmacological treatment interventions. On the other hand, available data on best treatment approach in this population are scarce and lack scientific evidence due to methodological limitations. The present study aims to perform a systematic review of the literature to facilitate the use of psychotropic drugs in clinical practice and better establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Very little scientific research has been reported regarding the safety and efficacy of psychoactive drugs for subjects with intellectual disability (Molina‐Ruiz et al, ; Reiss & Aman, ). It is known that subjects with intellectual disability tend to develop side effects with standard doses of medication, to have side effects overshadowed and to show a worse response to psychotherapeutic and psychopharmacological treatment (Molina‐Ruiz et al, ; Reiss & Aman, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very little scientific research has been reported regarding the safety and efficacy of psychoactive drugs for subjects with intellectual disability (Molina‐Ruiz et al, ; Reiss & Aman, ). It is known that subjects with intellectual disability tend to develop side effects with standard doses of medication, to have side effects overshadowed and to show a worse response to psychotherapeutic and psychopharmacological treatment (Molina‐Ruiz et al, ; Reiss & Aman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Very little scientific research has been reported regarding the safety and efficacy of psychoactive drugs for subjects with intellectual disability (Molina‐Ruiz et al, ; Reiss & Aman, ). It is known that subjects with intellectual disability tend to develop side effects with standard doses of medication, to have side effects overshadowed and to show a worse response to psychotherapeutic and psychopharmacological treatment (Molina‐Ruiz et al, ; Reiss & Aman, ). To improve the outcome of the treatment in this population, it was suggested to use the most effective minimal dose, to continue the psychiatric assessments, to monitor the side effects and to augment the treatment with behavioural interventions (Leon, Greenlee, Barber, Sabaawi, & Singh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential side effects associated with stimulant medications in adults with ADHD include poor appetite with weight loss, insomnia, nervousness, a mild increase in pulse and blood pressure, increased motor activities including tics and unwanted psychiatric effects such as irritability, dysphoria and social withdrawal (Molina‐Ruiz et al, 2017; Tarrant et al, 2018). In regular follow‐ups with Mary, she has not experienced any of these side effects.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Bu nedenle genel prensip, küçük dozlarla başlayıp, yavaş ilerlemek ve çoklu ilaç kullanımından kaçınmaktır. Genel olarak elimizdeki kanıtlar çok yetersiz olduğundan, farmakolojik müdahaleler risk-yarar analizi yaparak, kişi bazında planlanmalıdır (33) .…”
Section: Psikotrop Ilaç Kullanımıunclassified